METHOD OF INCREASING THE CAPACITY OF FIBER OPTIC TRANSMISSION SYSTEMS USING Y-SPLITTER - Kiyamov Rakhmatullo Ruzievich (Web of Journals Publishing, 2025)
The issue of increasing the capacity of fiber-optic transmission systems is relevant and has prospects for development in the future. The article discusses methods for increasing capacity and their scope of application, and also describes a method for increasing the capacity of fiber-optic transmission systems using Y-splitters.
Keywords: Mobile, information and communication, Y-splitters, fiber, attenuation, telecommunications, length of optical fiber.